The impact of financial solvency on the size of risks of insurance companies "Case Study" (Journal of Hama University, 2021)
The study aims to know the extent of the impact of financial solvency on the size of risks in the Kuwait Insurance Company listed on the Damascus Stock Exchange, and the published financial reports of the company during the period 2008-2019 were relied on, and the statistical package (SPSS) was used to test the extent of the impact of financial solvency on the size of risks . Financial solvency was measured using the three indicators according to the solvency margin system in the Syrian insurance companies issued by the Insurance Supervision Authority Resolution No. / 210 / for the year 2008, and the results of the study showed that the Kuwait Insurance Company has a good level of financial solvency to ensure facing the risk of failure of reinsurers. In fulfilling its obligations, in addition to that there is a positive significant impact of financial solvency indicators on the size of risks. The study recommended that the financial solvency be within the acceptable limits so that the funds are not left frozen without exploitation in the event there is a surplus in the solvency, and the companies are not exposed to the problems of inability to pay the benefits in the event there is a deficiency in the solvency, which affects the increase in risks in both cases, This can be done by providing the opportunity to increase the proportion of investment of the funds it possesses in areas that generate adequate and stable income, thus bringing interest to companies and reducing the risks of the insurance portfolio to a minimum.